Developing Software Patterns in Thai Supply Chain - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research aim were to design and to evaluate software patterns in Thai supply chain. Three steps of the research study were: reviewing literature to analyse and synthesize, designing the patterns, and evaluating the software patterns in Thai supply chain. The sample group included ten experts who specialized in supply chain and in information system The research tool was evaluation form to evaluate software patterns in Thai supply chain comprises six main elements, namely suppliers , component manufacturers, Distribution, Retailer and customer. The research result reported that ten experts agreed that the patterns was appropriate in the highly and the patterns to support sustainable software production.